Matcha green tea (MGT) inhibits the propagation of cancer stem cells (CSCs), by targeting mitochondrial metabolism, glycolysis and multiple cell signalling pathways - Bonuccelli, Gloria (Aging (Albany NY), 2018)
Matcha green tea (MGT) is a natural product that is currently used as a dietary supplement and may have significant anti-cancer properties. However, the molecular mechanism(s) underpinning its potential health benefits remain largely unknown. Here, we used MCF7 cells (an ER(+) human breast cancer cell line) as a model system, to systematically dissect the effects of MGT at the cellular level, via i) metabolic phenotyping and ii) unbiased proteomics analysis. Our results indicate that MGT is indeed sufficient to inhibit the propagation of breast cancer stem cells (CSCs), with an IC-50 of ~0.2 mg/ml, in tissue culture. Interestingly, metabolic phenotyping revealed that treatment with MGT is sufficient to suppress both oxidative mitochondrial metabolism (OXPHOS) and glycolytic flux, shifting cancer cells towards a more quiescent metabolic state. Unbiased label-free proteomics analysis identified the specific mitochondrial proteins and glycolytic enzymes that were down-regulated by MGT treatment. Moreover, to discover the underlying signalling pathways involved in this metabolic shift, we subjected our proteomics data sets to bio-informatics interrogation via Ingenuity Pathway Analysis (IPA) software. Our results indicate that MGT strongly affected mTOR signalling, specifically down-regulating many components of the 40S ribosome. This raises the intriguing possibility that MGT can be used as inhibitor of mTOR, instead of chemical compounds, such as rapamycin. In addition, other key pathways were affected, including the anti-oxidant response, cell cycle regulation, as well as interleukin signalling. Our results are consistent with the idea that MGT may have significant therapeutic potential, by mediating the metabolic reprogramming of cancer cells.